2021
DOI: 10.3389/fpsyt.2021.658934
|View full text |Cite
|
Sign up to set email alerts
|

Anosognosia in Early- and Late-Onset Dementia and Its Association With Neuropsychiatric Symptoms

Abstract: Background: The symptom anosognosia or unawareness of disease in dementia has mainly been studied in patients with late-onset dementia (LOD, ≥65 years), whereas little is known on whether it is also present in patients with early-onset dementia (EOD, <65 years). We aimed at investigating differences in anosognosia between LOD and EOD, by also studying its association with different clinical variants of EOD and the presence of neuropsychiatric symptoms.Methods: A total of 148 patients, 91 EOD and 57 LOD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
1
7
1
1
Order By: Relevance
“…Within this framework, one possibility is that alterations in memory self-awareness represent an early indicator of progressive decline toward AD dementia due to increased dysfunction of the DMN. This hypothesis is consistent with previous studies relating loss of awareness in AD with DMN connectivity (Mondragón et al, 2019(Mondragón et al, , 2021, but also with the relationship between anosognosia in AD with some neuropsychiatric disorders (Spalletta et al, 2012;Tondelli et al, 2021) which have also been associated with dysfunction of the DMN (Lee et al, 2020). When looking at the groups separately, we only observed a significant correlation between awareness and EM in the MCI individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Within this framework, one possibility is that alterations in memory self-awareness represent an early indicator of progressive decline toward AD dementia due to increased dysfunction of the DMN. This hypothesis is consistent with previous studies relating loss of awareness in AD with DMN connectivity (Mondragón et al, 2019(Mondragón et al, , 2021, but also with the relationship between anosognosia in AD with some neuropsychiatric disorders (Spalletta et al, 2012;Tondelli et al, 2021) which have also been associated with dysfunction of the DMN (Lee et al, 2020). When looking at the groups separately, we only observed a significant correlation between awareness and EM in the MCI individuals.…”
Section: Discussionsupporting
confidence: 92%
“…An overall interpretation of these two opposite behaviours is that they may form part of more general processes, such as the degree of attention speakers pay to their speech (Christenfeld and Creager 1996). We hypothesised above that the hyper-fluency in individuals with svPPA may be due to the reduced attention they pay to their speech, because of either strategic decisions (Postma 2000;Sahraoui et al 2015) or higher levels of anosognosia (Tondelli et al 2021), leading to decreased self-monitoring. It has already been reported that people with svPPA tend not to grasp for 'lost' words in a conversation (Marshall et al 2018), contrary to what is observed in the other two variants of PPA.…”
Section: Svppamentioning
confidence: 96%
“…Awareness is a multidimensional clinical symptom frequently observed in neurodegenerative dementia, such as frontotemporal dementia (FTD) or Alzheimer's disease (AD) type dementia. 1 Patients can be more or less unaware of disturbances in cognitive, behavioral, or daily functioning. Unawareness (or anosognosia) of memory difficulties was already observed in patients with mild cognitive impairment (MCI) who progressed to AD.…”
Section: Introductionmentioning
confidence: 99%